Gua dan Kawasan Karst, Daya Tarik Serta Ragam Fungsinya dalam Kehidupan Manusia - Nenggih Susilowati (Berkala Arkeologi Sangkhakala, 2009)
AbstractRock shelter and cave and also its karst environment are natural resources for the benefit of human life from the past until now. In the past, human has exploited natural resources for various purposes. Remains of past human activities at these sites are cultural resources that object of an archaeology research. The natural resources consisting in the archaeological sites is also exploited by human for a variety of other interests that conflict of interest occurs.